Environmental Performance Review: Kazakhstan - United Nations (United Nations, 2009)
This report examines the progress made by Kazakhstan in the management of its environment since it was first reviewed in 2000. It assesses the implementation of the recommendations in the first review and it covers issues of importance to the country concerning policymaking, planning and implementation, the financing of environmental policies and projects and the integration of environmental concerns into economic sectors. The report also emphasizes the promotion of sustainable development in Kazakhstan.